Brief Interventions for Risky Drinkers - Antoni Gual (Frontiers Research Topics, 2016)
Alcohol is the sixth leading risk factor for disability and premature death all over the world, and one of the leading causes of premature mortality in western societies; it is a leading risk factor for death in young and middle-age males. Heavy drinking accounts for about two thirds of the burden of disease attributable to alcohol. In the early 1980s, screening and brief interventions (SBI) in primary health care settings were proposed as effective strategies to identify risky drinkers and to help them reduce their drinking. Since then, a growing body of evidence, including several meta-analysis and Cochrane reviews, has shown the efficacy and effectiveness of SBI in primary health settings. However, demonstrating the effectiveness of SBI has not been insufficient to facilitate its general implementation in the routines of primary health care physicians, and in fact the dissemination of SBI has proven to be a difficult business. Qualitative and quantitative research has identified most of the facilitators and barriers for its implementation, and publicly funded research has been earmarked to address the dissemination problems worldwide. Some examples are the World Health Organization Phase III and Phase IV studies on the identification and management of alcohol-related problems in primary care, EU funded projects (PHEPA, AMPHORA, ODHIN, BISTAIRS), the UK SIPS trials and the SBIRT developments sponsored by the Substance Abuse & Mental Health Services Administration (SAMHSA) in the USA. The efficacy and effectiveness of SBI in primary health is now well established, but there are still some questions that remain unsolved: which practitioners should deliver them; what length should they be; is there a need for booster sessions; is there added value of a motivational approach? These questions, together with other relevant aspects of SBI, need ongoing research. In recent years, SBIs have been tested in settings other than primary health care, including hospitals, accident and emergency rooms, criminal justice, colleges and universities, social services and pharmacies. In some of those areas, the evidence is scarce (for example, pharmacies) while in others it is very promising (for example, students and hospitals). New technologies have also offered the possibility of online tools, and, in the last few years, different digital-based applications have been tested successfully as new ways to deliver effective SBIs to larger amounts of people. Brief interventions have also spread to drugs other than alcohol. This book aims to be an update of the state-of-the art of brief advice. It is a compilation of articles published by some of the most relevant researchers in the field in Frontiers in Psychiatry between 2014 and 2016.